Regulation of Adult Neurogenesis by Non-coding RNAs: Implications for Substance Use Disorders - Oliver, Robert J.; Mandyam, Chitra D. (Frontiers in Neuroscience, 2018)
The discovery of non-coding RNAs has been one of the central findings from early genomic sequencing studies. Not only was the presence of these genes unknown previously, it was the staggering disproportionate share of the genome that was predicted to be encoded by non-coding RNAs that was truly significant in genomic research. Over the years the function of various classes of these non-coding RNAs has been revealed. One of the first and enduring regulatory programs associated with these factors was development. In the neurosciences, the discovery of adult derived populations of dividing cells within the brain was equally substantial. The brain was hypothesized to be plastic only in its neuronal connectivity, but the discovery of the generation of new neurons was a novel mechanism of neuronal and behavioral plasticity. The process of adult neurogenesis resembles early neuronal development and has been found to share many parallels in the proper stages of specified genetic programs. Adult neurogenesis has also been found to play a role in learning and memory involved in particular hippocampal-dependent behaviors. Substance use disorders (SUDs) are an example of a behavioral condition that is associated with and possibly driven by hippocampal alterations. Our laboratory has determined that hippocampal adult neurogenesis is necessary for a rodent model of methamphetamine relapse. Due to the previous research on non-coding RNAs in development and in other brain regions involved in SUDs, we posit that non-coding RNAs may play a role in adult neurogenesis associated with this disorder. This review will cover the regulatory mechanisms of various classes of non-coding RNAs on the coordinated genetic program associated with adult neurogenesis with a special focus on how these programs could be dysregulated in SUDs.